ANALISIS PENGARUH TARIF STEVEDORING, CARGODORING, DAN RECEIVING/ DELIVERY TERHADAP VOLUME BONGKAR MUAT MAKANAN TERNAK - Herman Budi Sasono (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2006)
The implementation of reloading activity is based on the rule which is exist and behaved according to each port’s condition, where the training and supervising are done and consist of the government thoroughly, the reloading workers and the reloading company factor. In the reloading activity, any kind of problems and the consideration of reloading company expands large cost for reloading taxes which is consist of stevedoring, cargodoring, and receiving/ delivery, so it can decrease the export import volume. In addition to make efficiency, in reloading operation needs absolute plan, so it can make an effective work plan with an optimal result. Corporation between each person in the field or the person who take a hand in the administration will be influenced much from the reloading taxes problem. For the increasing reloading taxes to face the competition between company, international competition intervention, the economic condition which is unstable and the fast growing technology development are the external factors which make the company should find a new trick to functioned the human resources and the budget more effective and efficient. The aim of this research is to investigate the influence of stevedoring, cargodoring, and receiving/ delivery taxes toward pet feed reloading volume at Tanjung Perak Port, Surabaya in 1995 - 2004. The analysis which is used in this research are double linier regression. From this regression can be found Y = 203153,8 +16,128X1 – 484,036X2+ 224,570X3. Regression analysis also shows that all of the independent variable simultaneously have significant effect toward pet feed reloading volume at Tanjung Perak port Surabaya. Nevertheless, based on partial test, only stevedoring variable and cargodoring which have significant effect on reloading volume.